MRI amygdala volume in Williams syndrome - Capitão, Liliana (2011)
One of the most intriguing characteristics of Williams Syndrome individuals is their hypersociability. The amygdala has been consistently implicated in the etiology of this social profile, particularly given its role in emotional and social behavior. This study examined amygdala volume and symmetry in WS individuals and in age and sex matched controls. Magnetic resonance imaging scans were obtained on a GE 1.5-T magnet with 1.5- mm contiguous slices and were used to measure whole gray matter, white matter and cerebrospinal fluid volumes, as well as amygdala volume (right and left). Results revealed significantly reduced intracranial volume in individuals with WS, compared with controls. There were no differences between groups in absolute amygdalae volume, although there was a relative increase in amygdalae volumes, when adjusted for total intracranial content. There were no inter-hemispheric differences in amygdalae volumes in both groups. These results suggest a relative increase in amygdala volume in WS compared with healthy controls that likely reflects abnormal neurodevelopmental processes of midline brain structures.